Rehabilitation Professional and Patient Satisfaction with Telerehabilitation of Musculoskeletal Disorders: A Systematic Review. (2nd August 2022) - Amin, Junaid; Ahmad, Basaruddin; Amin, Salman; Siddiqui, Ammar Ahmed; Alam, Mohammad Khursheed
Abstract : Telerehabilitation offers an alternative healthcare delivery remotely in a patient's environment at a lower cost, better accessibility, and equivalent quality to the standard approach. Several studies had examined the effectiveness of telerehabilitation inpatients with musculoskeletal disorders, and although there is evidence that it is at least equally effective as the standard care, the patient and rehabilitation professional satisfaction with the delivery method is not conclusive. A systematic review was conducted to study the patients' and rehabilitation professionals' satisfaction with telerehabilitation for musculoskeletal disorders. A search for relevant studies on 29 April 2021 was carried out in Medline/PubMed, Scopus, and Web of Science (WOS). The search terms included "telerehabilitation, " AND "satisfaction" AND "musculoskeletal disorders, " "telehealth, " "telemedicine, " "patient experience, " and "pain". Fifteen eligible studies with 12, 341 patients were included in this systematic review. A report was included if it (a) assessed the satisfaction of patients or professionals or both as one of the outcomes of a telerehabilitation intervention, (b) included adults 18 years and above with musculoskeletal disorders, and (c) is an intervention study using a quantitative approach. The quality of studies was assessed using the critical appraisal checklist tool developed by Joanna Briggs Institute (JBI). Most of the studies reported that patients were satisfied with both telerehabilitation and face-to-face intervention. However, few studies reported that patients were more satisfied with telerehabilitation compared to face-to-face of intervention. Patients in one study had preferred the incorporation of telerehabilitation and face-to-face sessions. Two of three studies had reported overall satisfaction with telerehabilitation by the professionals. Overall, there is evidence that patients and rehabilitation professional are satisfied with telerehabilitation compared to face-to-face consultation.